A 71-YEAR-OLD MAN WITH UNSTABLE ANGINA PECTORIS AND DM TYPE 2 (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Angina pectoris is chest pain caused by insufficient blood and oxygen flow to the cor. Worsening chest pain that occurs at rest or with light activity without damage to the cor muscle is called unstable angina pectoris (UAP). According to the World Health Organization, in the United States every year there are one million patients hospitalized due to UAP where 6-8% of them have non-fatal infarction attacks or die within 1 year after the diagnosis is made. This case report describes a 71-year-old man who came to the emergency room with complaints of shortness of breath for the past 3 days and worsened when he was admitted to the hospital in the morning. Shortness of breath occurs when the patient is doing activities. Shortness of breath accompanied by pain like being crushed in the left chest and does not spread. Complaints accompanied by nausea and cold sweat. Physical examination found VAS 5 pain, percussion of the cor revealed cardiomegaly, auscultation of the chest revealed fine crackles at the bases of both lungs. Investigations revealed a random blood sugar test of 340 mgdL-1, the EKG found T-wave inversion in leads V1-V5, while laboratory tests showed Troponin T of 0.21 ngmL-1. Chest X-ray examination showed cardiomegaly and pulmonary edema. Echocardiographic examination revealed segmental hypokinetic impressions, left ventricular and right ventricular systolic function were good with an ejection fraction of 59.5%. Treatment of the patient in this case was given nasal cannula oxygen 3 liters per minute, Fondaparinux injection 2.5 mg once a day subcutaneously for five days, Furosemide injection 20 mg every 12 hours, Glimepiride 2 mg once a day, Metformin 500 mg every 12 hours, Ramipril 5 mg once a day, Bisoprolol 2.5 mg once a day, Clopidogrel 300 mg continued 75 mg once a day, Aspirin 160 mg continued 80mg once a day, Atorvastatin 20 mg once a day, and Nitrokaf retard 2.5 mg every 12 hours.
Keywords: DM type 2; unstable angina pectoris